Peningkatkan Minat Baca Bagi Siswa Melalui Gerakan Literasi Sekolah - Alfin Maskur (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2023)
Reading is an activity that serves as a fundamental necessity in daily life. It is an effort to acquire information, enhance knowledge, and improve skills. Low reading interest among students can be attributed to a lack of understanding of the importance of reading benefits, insufficient self-motivation, and a lack of support from the surrounding environment. Therefore, a school literacy program needs to be implemented to serve as a means for students to explore, understand, and deepen the knowledge acquired in school. Through the literacy school movement, it is hoped that schools can become enjoyable and child-friendly learning environments, enabling students to manage information and knowledge, thus broadening their understanding. The purpose of this article is to examine the content of the chosen article to assess the results of implementing the school literacy program in an effort to increase students' reading interest. The analysis of several writings and journals reveals that the School Literacy Movement is executed in three stages: familiarization, development, and learning. There are various activities aimed at enhancing children's reading interest through the school literacy movement, including establishing a habit of reading for 15 minutes before the lesson starts, providing a reading corner, creating a literacy tree in the classroom, offering a comfortable library service, empowering school bulletin boards, school monetization, and organizing literacy competitions between classes.